Pengaruh Media Game Smart Box terhadap Hasil Belajar Siswa pada Materi Nilai-nilai Pancasila Kelas IV Madrasah Ibtidaiyah Swasta Khansa Khalifah - Popy Handayani Br Surbakti; Nizmi Putri; Mastari Ramadhani (Medan Resource Center, 2025)
This study investigates the effect of Smart Box game media on students’ learning outcomes in the topic of Pancasila values among fourth-grade students at Madrasah Ibtidaiyah Swasta Khansa Khalifah. The research addresses the problem of low engagement and suboptimal achievement when conventional lecture methods are used in Civics-related instruction. Using a quantitative approach with a quasi-experimental design, the study involved a population of 40 students, with class IVA (n = 20) assigned as the experimental group and class IVB (n = 20) as the control group, selected through simple random sampling. Data were collected through observation, interviews, tests, and documentation, and were further examined for validity, reliability, normality, and homogeneity. The findings indicate a substantial difference in posttest scores between the control class (M = 68.00) and the experimental class (M = 89.75). Normality and homogeneity tests confirmed that the data met the assumptions for parametric analysis, and the Independent Samples Test yielded a significance value (2-tailed) of 0.000 (< 0.05). These results demonstrate that Smart Box game media has a significant and positive impact on student learning outcomes in Pancasila values.